Is bouldering-psychotherapy a cost-effective way to treat depression when compared to group cognitive behavioral therapy - results from a randomized controlled trial - Larissa Schwarzkopf; Lisa Dorscht; Ludwig Kraus; Katharina Luttenberger (BMC, 2021)
Abstract Background Bouldering-Psychotherapy (BPT) has proven to effectively reduce depressive symptoms, but evidence on its cost-effectiveness is lacking. Corresponding information is paramount to support health policy decision making on a potential implementation of BPT in routine care. Methods Using data from the German KuS trial BPT was compared with group Cognitive Behavioral Therapy (CBT). Severity of depression symptoms at end of the intervention was operationalized via Montgomery-Asberg Depression Rating Scale (MADRS) and Patient Health Questionnaire (PHQ-9). Adopting a societal perspective, direct medical costs and productivity loss were calculated based on standardized unit costs. To determine incremental cost-effectiveness ratios (ICER) and cost-effectiveness-acceptance curves (CEAC), adjusted mean differences (AMD) in costs (gamma-distributed model) and both effect parameters (Gaussian-distributed model) were obtained from 1000 simultaneous bootstrap replications. Results BPT was related to improved effects (AMDs: MADRS -2.58; PHQ-9: − 1.35) at higher costs (AMD: +€ 754). No AMD was significant. ICERs amounted to €288 per MADRS-point and €550 per PHQ-9-point. For both effect parameters about 20% of bootstrap replications indicated dominance of BPT, and about 75% larger effects at higher costs. At hypothetical willingness to pay (WTP) thresholds of €241 (MADRS) and €615 (PHQ-9) per unit of change BPT had a 50% probability of being cost-effective. Conclusion BPT is a promising alternate treatment strategy which - in absence of established WTP thresholds for improving symptoms of depression - cannot unambiguously be claimed cost-effective. Further studies defining subgroups that particularly benefit from BPT appear paramount to delineate recommendations for an efficient prospective roll-out to routine care.